Efficiency of fumigation with 100% methyl bromide in grapefruit infested by Anastrepha spp. - De Santiago-Meza, Joel; Frías-Treviño, Gustavo Alberto; Aguirre-Uribe, Luis Alberto; Vázquez-Rojas, Tito; Almaraz-Asis, Victor Manuel (Revista Mexicana de Ciencias Agrícolas, 2025)
The response of fruit fly (Anastrepha spp.) larvae to fumigation with 100% methyl bromide was evaluated in naturally infested grapefruits. The above was carried out at the end of the 2021 production cycle in the citrus-growing region of Nuevo León, Mexico; to this end, grapefruits (Citrus paradisi) infested with fruit flies were harvested. The collected fruits were divided into three batches; two were treated in a fumigation chamber with methyl bromide at 24 g m-3 for a two-hour exposure and the other served as a control. After fumigation, one of the fumigated batches was refrigerated at 5 °C, while the other was kept at room temperature between 19 and 24 °C. The percentage of live larvae was evaluated 5, 24, 48 and 72 h after fumigation in 30 fruits from each batch. Eighty-nine to 94% of larvae stopped moving 72 h after fumigation. Using the exponential model fitted to the data, it was estimated that all larvae lose their ability to move 120-144 h after fumigation (5-6 days). Refrigeration increased the percentage of larvae with movement, but this effect was lost 48 h after fumigation. These results indicate that the effectiveness of fumigation on the host fruit of Anastrepha spp. with methyl bromide can be assessed with certainty 5-6 days after treatment.
Keywords: Anastrepha spp.; fumigation; grapefruit; methyl bromide